PERAMALAN JUMLAH MAHASISWA BARU DENGAN PENDEKATAN REGRESI LINIER - Yulia Utami; Desi Vinsensia; Aura Nissa; Sulastri Sulastri (Jurnal Teknik Informatika C.I.T Medicom, 2022)
Forecasting models are the result of developments in the field of science and technology that provide convenience in predicting future events. This paper aims to develop a linear regression model to predict the number of new students in the next year. The data to be used in this study is the total of students majoring in informatics engineering and information management during the last 5 years. Based on result obtained the number of student for department of Informatics Engineering is 198 people with a MAPE (Mean Absolute Percentage Error) score of 16.5%, and for the new students department of Informatic Management is 8 people with a MAPE score of 16.1%.